EXCAVATIONS IN THE ANDENES OF ANDAMARCA, NEGROMAYO RIVER BASIN, LUCANAS, AYACUCHO - Aguirre-Morales P., Manuel (2009)
This communication describes a preliminary part of the results of the excavations conducted in 2005 in several sectors of andenes near the town of Andamarca, District of Carmen Salcedo, Province of Lucanas, in Ayacucho Region. I describe the andenes investigated and the criteria taken into account in the development of a typology of andenes capable of distinguishing the andenes built by the Huari of those built by the Incas. In order to plot these differences, are some examples from our excavations and presents some preliminary hypotheses about the construction, production and maintenance of andenes. Finaly, I analyze the problems of archaeological research on the andenes of their time arguing about the initial construction, rebuilding, and the nature of the crops that they produced in ancient times as well as the challenges of rehabilitation and production andenes today abandoned in the Central Andes.